Pengaruh Kualitas Air Kolam Terpal terhadap Pertumbuhan Ikan Lele Dumbo (Clarias gariepinus) - Suci Nurul Hidayati; Saimul Laili; Hari Santoso (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2021)
ABSTRACT Water quality is what describes the suitability or suitability of water for certain uses. Dumbo catfish (Clarias gariepinus) is one type of fish that has been widely cultivated in Indonesia. The catfish habitat is very flexible, can be cultivated with high stocking densities, very rapid growth, and can live in environments with low oxygen levels, because it has an additional respiratory organ, namely the arborescent organ. This study aims is to compare the length and weight of Dumbo catfish in relation to water quality parameters in pools that made from container of tarpaulin with different densities. The method used in this research is the survey method by collecting primary data on tarpaulin pond water quality and catfish growth measurements, with densely spreading 500 and one thousand per pond of maintenance. The results of the study obtained the range of parameters of tarpaulin pond water quality parameters meeting the optimum standard for the growth of African catfish (C. gariepinus) which is still in accordance with the quality standards according to PP No. 02 of 2011 class III for freshwater fish farmers. The growth of catfish in ponds with 1000 head spreads faster with the average fish length increase of 15.71 cm weighing 14.85 g, compared with a 500-tailed pond with an average length of 15.61 cm and a weight of 14.83 g. Keywords: Quality, Growth, Catfish dumbo ABSTRAK Kualitas air adalah apa yang menggambarkan kesesuaian atau kecocokan air untuk penggunaan tertentu. Lele dumbo (Clarias gariepinus) merupakan salah satu jenis ikan yang sudah banyak dibudidayakan di Indonesia. Habitatnya ikan lele sangat fleksibel, dapat dibudidayakan dengan padat penebaran tinggi, pertumbuhannya sangat pesat, dan bisa hidup dilingkungan dengan kadar oksigen rendah, karena mempunyai organ pernapasan tambahan yaitu arborescent organ. Penelitian ini bertujuan untukmembandingkan pertambahan panjang dan bobot ikan lele dumbo kaitannya dengan parameter kualitas air pada kolam wadah terpal dengan kepadatan yang berbeda.Metode yang digunakan penelitian adalah metode survei dengan pengumpulan data primer kualitas air kolam terpal dan pengukuran pertumbuhan ikan lele, dengan padat penebaran lima ratus dan seribu ekor per kolam pemeliharaan. Hasil penelitian mendapatkan nilai kisaran parameter kualitas air kolam terpal memenuhi standar optimum bagi pertumbuhan ikan lele Dumbo yang masih sesuai dengan standar baku mutu menurut PP No. 02 Tahun 2011 kelas III untuk pembudidaya ikan air tawar. Pertumbuhan ikan lele pada kolam dengan tebaran 1000 ekor lebih cepat dengan hasil rerata pertambahan panjang ikan sebesar 15,71 cm dengan bobot 14,85 g, dibandingkan dengan kolam tebaran 500 ekor dengan rerata pertambahan panjang 15,61 cm dan bobot 14,83 g. KataKunci: Kualitas, Pertumbuhan, Ikanlele dumbo